2012
DOI: 10.3758/s13414-012-0308-x
|View full text |Cite
|
Sign up to set email alerts
|

Negative emotional photographs are identified more slowly than positive photographs

Abstract: In three experiments, we investigated whether the emotional valence of a photograph influenced the amount of time required to initially identify the contents of the image. In Experiment 1, participants saw a slideshow consisting of positive, neutral, and negative photographs that were balanced for arousal. During the slideshow, presentation time was substantially limited (60 ms), and the images were followed by masks. Immediately following the slideshows, participants were given a recognition memory test. Memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…The projections from the amygdala to the visual cortex are magnocellular. Bocanegra and Zeelenberg (2009) and Becker (2012) suggested that these magnocellular projections shift the balance in the visual system from ventral to dorsal processing, because the dorsal visual pathway has primarily magnocellular input, while the ventral path relies on parvocellular input (Maunsell, Nealey, & DePriest, 1990). This serves behavioral motivational functions, because the dorsal pathway translates valence into automatic approach—or avoidance—responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The projections from the amygdala to the visual cortex are magnocellular. Bocanegra and Zeelenberg (2009) and Becker (2012) suggested that these magnocellular projections shift the balance in the visual system from ventral to dorsal processing, because the dorsal visual pathway has primarily magnocellular input, while the ventral path relies on parvocellular input (Maunsell, Nealey, & DePriest, 1990). This serves behavioral motivational functions, because the dorsal pathway translates valence into automatic approach—or avoidance—responses.…”
Section: Discussionmentioning
confidence: 99%
“…However, conscious taskrule guided behavior-such as the gender classification in our task-requires processing in the ventral visual pathway. Consequently, conscious rule-based processing is slowed down for affective-especially negative-pictures (Becker, 2012;Maljkovic & Martini, 2005). We assume that time-based expectancy results in a temporally specific preemptive activation of the ventral pathway to counteract its anticipated deficit.…”
Section: Theoretical Explanationsmentioning
confidence: 99%
“…The results indicate that emotional prosody modulates word processing. There have also been claims that processing differences exist between positive and negative emotions, whereby positive emotions give a processing advantage in different contexts (cf., e.g., Becker, 2012;Nobata, Hakoda, & Ninose, 2010). The present study of positive vs. negative emotions aimed to discover the effects of types (dimensions) of emotion.…”
Section: Cross-modal Primingmentioning
confidence: 99%
“…In other words, attention is effectively captured by a distracting, task-irrel-evant emotional event, and causes attentional disengagement from the originally attended task (Gupta, Hur, & Lavie, 2016;Nummenmaa, Hyönä, & Calvo, 2006). An emotional event presented prior to, simultaneously with, or even after a neutral event disrupts processing of other neutral events, which has been attributed to an instinctive and involuntary attentional shift toward those emotional events (Becker, 2012;Choisdealbha et al, 2017;Fernández-Martín & Calvo, 2016;Krug & Carter, 2012;Öhman, Flykt, & Esteves, 2001;Oca et al, 2012;Sakaki, Gorlick, & Mather, 2011). Likewise, eye movement studies illustrate that initial fixations are more likely to land on emotional information (Adolphs, Tranel, & Buchanan, 2015;Calvo & Lang, 2005), and that semantic details of emotional information can be picked up even in peripheral vision (Bocanegra & Zeelenberg, 2009;Calvo et al, 2008).…”
Section: Introductionmentioning
confidence: 99%